A Study of Perception of International Students on Quality of Malaysian Cars (Malaysian Management Journal, 2014)
This paper examines how international students in a local public institution perceived the quality of Malaysian-made cars and whether the country of origin is an important factor in determining the purchase decision of a car. A total of 176 full-time registered international students from 12 countries participated as respondents in this research. A purposive sample was used in this research whereby respondents were asked to complete a self-administrated questionnaire. The findings supported the literature which indicated that most respondents have a more favourable perception of cars made in the developed countries than cars made in developing countries. The influence of country of origin, also known as the â€œmade inâ€ effect, has been broadly defined as the positive or negative influence that a countryâ€™s product of manufacture may have on consumersâ€™ decision processes or subsequent behaviour. The result of this research showed that the effect of country of origin is discernable among the respondents.